2014
DOI: 10.1039/c4cp02362e
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid ion structures in the gas phase

Abstract: Nucleic acids are diverse polymeric macromolecules that are essential for all life forms. These biomolecules possess a functional three-dimensional structure under aqueous physiological conditions. Mass spectrometry-based approaches have on the other hand opened the possibility to gain structural information on nucleic acids from gas-phase measurements. To correlate gas-phase structural probing results with solution structures, it is therefore important to grasp the extent to which nucleic acid structures are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 164 publications
2
22
0
Order By: Relevance
“…However due to the gentleness and ease of ionizing DNA in negative ion mode, ESI-MS has long been used to detect delicate DNA bindings, including non-covalent attachment of molecules to DNA [28] and for investigation of binding stoichiometries to DNA [29]. Gas phase ESI-MS data for binding stoichiometry studies has also been experimentally shown to agree with high fidelity to solution phase data [30], though some fragmentation of canonically paired DNA oligomers may occur depending on the instrumental conditions employed [31,32]. Due to the considerably higher strength of Ag + -mediated pairings than WC pairings [23], we expect minimal fragmentation for these non-canonical, metal-bridged products and gas-phase distributions that are good approximations to solution phase abundances.…”
Section: Resultsmentioning
confidence: 99%
“…However due to the gentleness and ease of ionizing DNA in negative ion mode, ESI-MS has long been used to detect delicate DNA bindings, including non-covalent attachment of molecules to DNA [28] and for investigation of binding stoichiometries to DNA [29]. Gas phase ESI-MS data for binding stoichiometry studies has also been experimentally shown to agree with high fidelity to solution phase data [30], though some fragmentation of canonically paired DNA oligomers may occur depending on the instrumental conditions employed [31,32]. Due to the considerably higher strength of Ag + -mediated pairings than WC pairings [23], we expect minimal fragmentation for these non-canonical, metal-bridged products and gas-phase distributions that are good approximations to solution phase abundances.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, besides the classical and widely known double‐stranded DNA sequence (duplex), a plethora of other helical structures can be found, such as hairpin, pseudoknot, triplex, cruciform (Holliday junction), and G‐quadruplex structures. Most of these DNA conformations have been studied by IM–MS and molecular dynamics, highlighting a more dynamic and complex behavior in the gas‐phase as compared to proteins .…”
Section: Application Of Ion Mobility Spectrometry To the Characterizamentioning
confidence: 99%
“…One chain terminus then gets expelled into the vapor phase, followed by stepwise sequential ejection of the remaining protein and separation from the droplet [19, 20]. Despite its success in explaining the ionization of unfolded protein chains, the CEM is unlikely to apply to nucleic acid chains because their hydrophobic and hydrophilic moieties are homogenously distributed along the chain [21]. …”
Section: Introductionmentioning
confidence: 99%